Work Engagement And Quality Of Work Life: The Mediation Role Of Workplace Happiness - Barkhowa, Mokhammad Khukaim; Yudhatama, Mahendra Arya (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
A dignified human being is a human being who can enjoy a long, healthy life and lead a productive life. The impact of covid 19 is 10.45%, or 16,648 workers have reduced working hours due to covid-19. This scientific study investigates how quality work of life affects work engagement with workplace happiness as mediation. The important thing from this research is that it can expedite the activities of the working-age population in the City of Salatiga and reduce the impact of Covid 19, one of which is reducing working hours, reducing anxiety at work, creating happiness at work, and helping in terms of increasing the Human Development Index in the City of Salatiga. A sampling of this study uses calculations with the Slovin formula with a sample size of 100 employees. The analysis technique for this study uses the Smart Partial Least Square (PLS) 3.0 tool. The results of the survey show that quality of work life statistically has a positive and significant effect on workplace happiness, workplace happiness statistically has a positive and significant impact on work engagement, and quality of work life statistically has a positive and significant impact on work engagement mediated by workplace happiness